Nove anos de pesquisa: estudo longitudinal acerca da fluoretação das águas de abastecimento público de Birigui, SP - Santos, Luis Felipe Pupim dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Maintenance of adequate levels of fluoride in public water supply is essential for maximum benefit in the dental caries prevention and minimal risk of dental fluorosis. The aim of this study was to analyze the concentrations of fluoride in public water supply of the Birigui, SP, which has a complex water distribution system. The amount and location of water sources were identified and water samples were collected, monthly in 42 points previously established, in the period of 2004 to 2013. The analyses were done in the laboratory, by an ion analyzer coupled to a specific electrode for fluorine. The water system consists of 10 semi-artesian wells; water treatment station; and 02 shallow wells of alternative sources. The range considered for maximum benefit and minimum risk was from 0.55 to 0.84 mg F / L. From a total of 3131 samples analyzed, 78% ranged from 0.55 to 1.2 mg F / L, values considered within the range that does not cause damage to the health. It was noted that 6,6% of the samples corresponded to greater than 1.2 mg F / L, and these results from deep wells. Alternative sources were not fluoridated. It was concluded that most of the points presented appropriate levels of fluoride, however deep wells showed high concentrations

A manutenção dos teores adequados de flúor nas águas de abastecimento público é indispensável para benefício máximo na prevenção da cárie dentária e risco mínimo de fluorose dentária. O objetivo neste trabalho foi analisar as concentrações de flúor nas águas de abastecimento público do município de Birigui, SP, que possui uma complexa rede de distribuição de água. A quantidade e a localização de fontes de abastecimento foram identificadas e amostras de água foram coletadas mensalmente em 42 pontos previamente estabelecidos, no período de 2004 a 2013. As análises foram efetuadas em laboratório, por meio de um analisador de íons acoplado a um eletrodo específico para flúor. O sistema de água é constituído por 10 poços artesianos/semi-artesianos; Estação de tratamento; e 02 poços superficiais de fontes alternativas. O intervalo considerado de máximo benefício e risco mínimo foi de 0,55 a 0,84 mg F/L. Do total de 3131 amostras analisadas, 78% estavam no intervalo entre 0,55 a 1,2 mg F/L, valores considerados dentro da faixa que não causa danos à saúde. Notou-se que 6,6% do total de amostras corresponderam aos resultados maiores que 1,2 mg F/L, sendo estes provenientes de poços profundos. As fontes alternativas não eram fluoretadas. Concluiu-se que a maioria dos pontos estava com teores adequados, entretanto os poços profundos apresentaram altas concentrações
Keywords: Flúor; Saúde bucal; Fluoretação; Fluorine